Safety nets, gap filling and forests: a global-comparative perspective - Wunder, Sven; Börner, J.; Shively, G.E.; Wyman, M. (Elsevier, 2014)
In the forest–livelihoods literature, forests are widely perceived to provide both common safety nets to shocks and resources for seasonal gap-filling. We use a large global-comparative dataset to test these responses. We find households rank forest-extraction responses to shocks lower than most common alternatives. For seasonal gap-filling, forest extraction also has limited importance. The minority of households using forests for coping is asset-poor and lives in villages specialized on forests, in particular timber extraction. Overall, forest resources may be less important as a buffer between agricultural harvests and in times of unforeseen hardship than has been found in many case studies.